Analisis Pengaruh Harga: Studi Kasus Terhadap Keputusan Pembeli Makanan Tradisional Palembang Di Pasar 26 - Sherly Malini; Abdul Rahman (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The city of Pempek as the capital city of South Sumatra Province is well-known as the word "empek-empek" which has the potential to develop food tourism, considering that some of the typical folk foods of this area are of interest to local residents and migrants, including tourists. For consumers, prices are all forms of monetary costs sacrificed by consumers to obtain, own, utilize a number of combinations of goods and services from a product. Many consumers use prices as an influence on purchasing decisions